The Effect of Partial Dose and Treatment Area in the Activity of Some Insecticides on Larvae and Adult of Confused Flour Beetles Tribolium confusum Duval (Coleoptera; Tenebrionidae): وفاء عبد يحيى - AL-Raho, Wafa Abid Yehya (Journal of Kerbala for Agricultural Sciences, 2018)
The results of studying partial dose and treatment area showed the effect of insecticides: zorosuper Ec (36gm/liter). Avaunt Sc (150gm/liter) and Omite Ew (57%) in the mortality percentage of larvae and adults of confused flour beetles and also showed the superiority of insecticides zorosuper and Avaunt on the insecticide Omite in giving 100% mortality percentage of larvae. while the insecticide Avaunt gave the maximum mortality percentage of adults 100%. Results of partial dose of the studied insecticides showed that there is a significant effect when treating with 3/4 dose (0.75 ml/liter) by using Zorosuper on larvae. where it gave 99% mortality rate. 86.67% for each Avaunt and Omite. respectively. Concerning studying the effect of partial surface treatment. zorosuper insecticide gave the maximum mortality percentage of adults reached 99% when treating the surface completely, where it gave 92.33% mortality rate percentage on larvae when treating the surface completely. .